MANAGERIAL POWER AND EXECUTIVE PAY - Jonathan Gihon, Justin
This Final Project focuses on the significant role of managerial power that has an extended effect on executive compensation. The executive pay issue in the industry has reached the optimal attention in the industry for several years. The rise of executive pay concerns have risen because of a lack of understanding about the high executive pay for the CEOs. Moreover, Under the contract approach for executive compensation, which this research is about, executive compensation aims to increase shareholder value. However, in some cases, the shareholders are sometimes not allowed or even neglected in executive pay agreements. In contrast, executives in some cases have the power to control their own compensation and payments. Furthermore, leads to an inefficient pay structure because of the suboptimal incentives that benefit the executives rather than the company itself that causes a decrease in shareholder value. Then, issues like Netflix shareholders rejecting the CEO Pay packages (A. Weprin, 2023) and the way UK companies prepare for battles with their shareholders about executive compensation (Daniel and Harret, 2022) surfaces. It leads them to question what are the measures, merit or even consideration on the high executive pay whether it is aligning with the company performance. The process of producing compensation agreements, mostly leave the managers to have an influence in shaping their own compensations. Therefore, to understand the high executive compensation, people need to understand the managerial power the executives have in the organization. Moreover, understanding the mechanisms through which managerial power influences compensation outcomes has become paramount. This research will seek deep into the depths of FTSE 100 and S&P 500 companies in recent years (2018-2023) to find the interplay of managerial power and executive compensation. This research concludes that the managerial power is a pivotal role in the agreement of executive compensation and it could not be neglected in any parts of the executive pay agreements or even the whole corporate governance.